Efeitos da abertura do mercado externo em arranjos produtivos locais de base agroindustrial: o caso dos produtores de mamão do Espírito Santo. - Santos, Fabio Lyrio (2007)
In the last years, public and private agents have concentrated efforts and placing resources in action programs to the local productive arrangements (LPAs), organizational formations that allow the micro and small-sized enterprises (MSEs) survival and growth. The rescue of the MSEs role in the regions and countries development process happens in a time of resetting of the economic, social and political systems evolution spaces, remodeling of the production systems with the collective valuation, globalization and local protagonism. One of the main goals of these action programs is the insertion of MSEs in the international markets. Thus, the economic growth of firms and the sustainable development along the production chain should be bigger. The object of study of this research was the enterprises of the Espírito Santo State LPA of papaya, mainly centered in Linhares city. This region has little more than 200 producing properties and a set of linked entities that include education, research and technical institutions, financing agencies, trade associations, category entities and others support institutions. The aim of this research was to identify the collective benefits generated to the arrangement after the opening of the United States market, in 1998, and to verify how these benefits were individualized and absorbed by the local firms. The research was carried out under qualitative approach and the used method was the case study. Twenty five interviews were carried out, being fifteen with MSEs and small farm households, five with larger companies, and others five with support institutions. The results evinced that the exportations stratified the firms in two groups: one with the medium and large-sized exporting firms and another one with the non-exporting MSEs and farm households. Despite this, the generated benefits were not restricted to the exporting firms group, being spread to the other firms and links of the arrangement. The exportations increased the economic, social and environmental sustainable of the local papaya cultivation and stimulated the adoption of product and processes innovations, improving the competitiveness of firms and profiting its economic growth. The planted area, the production volume and the amount of companies enlarged, as well as the job offer and the income.